Sex based analysis of the impact of red blood cell transfusion and vascular or bleeding complications related to TAVI – The TRITAVI-Women Study - Rodriguez-Gabella, Tania; Zimarino, Marco; Barbanti, Marco; Testa, Luca; Capodanno, Davide; Stefanini, Giulio G.; Radico, Francesco; Fabbiocchi, Franco; Piva, Tommaso; Saia, Francesco; Biancari, Fausto; Eskola, Markku; et al. (International journal of cardiology, 2021)
Women present specific risks for transcatheter aortic valve replacement (TAVI) but there are scarce sex-based analysis. The aim of this study was to explore the risk of vascular/bleeding complications in females vs. males that underwent TAVI and the impact of red blood cell (RBC) transfusion. TRITAVI-Women is a retrospective analysis in 13 European institutions. Propensity score based on pairs of different sex was performed and global outcomes, vascular/bleeding risk factors were determined. Afterwards, the female population of the study was divided into two groups according to the need of RBC transfusion and the risk for mortality, AKI, MI, stroke at 30-days and at 1-year were compared as a combined endpoint (primary endpoint) and separately (secondary endpoints). The global study population included 5837 patients. Females presented more advanced NYHA class, chronic kidney disease, and baseline anemia. Vascular/bleeding complications and RBC transfusion were more common in women. However, 1-year mortality was lower for women in the matched cohort (8.1% vs.10.3%, p = 0.028). The need for RBC transfusion was an independent predictor of higher incidence of the primary endpoint at 30-day and 1-year. The main predictor of RBC transfusion in women was the presence of baseline anemia. Women present lower risk of mortality than men at 1-year follow up, but not at 30-day due to higher rates of vascular/bleeding complications. RBC transfusion was also more often required in women and was an independent predictor or poorer outcomes. The treatment of pre-existing anemia before TAVI might improve the short-term results in women. •Women present similar 30-days risk of mortality compared to men after transcatheter aortic valve implantation.•Women present lower 1-year risk of mortality compared to men after transcatheter aortic valve implantation.•Greater rate of vascular/bleeding complications, and RCB transfusion might explain worse outcomes of women at short-term.•Baseline anemia was more common in women and predicted a greater need for RBC transfusion.